The Really Long‐Run Performance of Initial Public Offerings: The Pre‐Nasdaq Evidence - Gompers, Paul A.; Lerner, Josh (Journal of Finance, 2003)
ABSTRACT Financial economists have intensely debated the performance of IPOs using data after the formation of Nasdaq. This paper sheds light on this controversy by undertaking a large, out‐of‐sample study: We examine the performance for five years after listing of 3,661 U.S. IPOs from 1935 to 1972. The sample displays some underperformance when event‐time buy‐and‐hold abnormal returns are used. The underperformance disappears, however, when cumulative abnormal returns are utilized. A calendar‐time analysis shows that over the entire period, IPOs return as much as the market. The intercepts in CAPM and Fama–French regressions are insignificantly different from zero, suggesting no abnormal performance.